2012
DOI: 10.1111/j.1755-6686.2012.00324.x
|View full text |Cite
|
Sign up to set email alerts
|

How Young People Cope With Chronic Kidney Disease: Literature Review

Abstract: More qualitative research is vital to retrieve 'real-life' perceptions from young people coping with kidney disease to identify how care should be made more explicit for them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Several studies have found that peer support increases self‐efficacy amongst young people with chronic disease (Muhammad et al . ; Rhee et al . ; Sattoe et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have found that peer support increases self‐efficacy amongst young people with chronic disease (Muhammad et al . ; Rhee et al . ; Sattoe et al .…”
Section: Discussionmentioning
confidence: 99%
“…Being together with other young people with kidney disease in the youth clinic contributed to higher self-efficacy by believing in own abilities to deal with life with kidney disease. Several studies have found that peer support increases self-efficacy amongst young people with chronic disease (Muhammad et al 2012;Rhee et al 2012;Sattoe et al 2013;Kohut et al 2014). Most of these studies are quantitative; together with our findings, it is shown that peer support is a positive contribution to the way young patients meet challenges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, young people with CKD are also subject to feelings of helplessness, a perceived lack of control and a negative health outlook, resulting in failure of coping strategies. Personal perspectives from this population would help fill a gap in knowledge and inform future care (Muhammad et al 2012a).…”
Section: B I O D a T Amentioning
confidence: 99%
“…The interview guide was developed from previously published literature (Muhammad et al 2012a(Muhammad et al , 2012b, and included questions on living and coping, family and friends, plus coping and planning. Supplemental Table S1 outlines the interview guide and the semi-structured questions.…”
Section: Interview Guide and Semi-structured Questionsmentioning
confidence: 99%